Increased Visual Stimulation Systematically Decreases Activity in Lateral Intermediate Cortex - Nasr, Shahin (Cereb Cortex, 2015)
Previous studies have attributed multiple diverse roles to the posterior superior temporal cortex (STC), both visually driven and cognitive, including part of the default mode network (DMN). Here, we demonstrate a unifying property across this multimodal region. Specifically, the lateral intermediate (LIM) portion of STC showed an unexpected feature: a progressively decreasing fMRI response to increases in visual stimulus size (or number). Such responses are reversed in sign, relative to well-known responses in classic occipital temporal visual cortex. In LIM, this “reversed” size function was present across multiple object categories and retinotopic eccentricities. Moreover, we found a significant interaction between the LIM size function and the distribution of subjects' attention. These findings suggest that LIM serves as a part of the DMN. Further analysis of functional connectivity, plus a meta-analysis of previous fMRI results, suggests that LIM is a heterogeneous area including different subdivisions. Surprisingly, analogous fMRI tests in macaque monkeys did not reveal a clear homolog of LIM. This interspecies discrepancy supports the idea that self-referential thinking and theory of mind are more prominent in humans, compared with monkeys.